Integrating genome and transcriptome analysis to decipher balanced structural variants in unsolved cases of neurodevelopmental disorders - Mellone, Simona; Spano, Alice; Vurchio, Denise; Borgonovi, Giulia; Ugonotti, Alessandro; Paglino, Giulia; Bianco, Alba; Ronzani, Sara; Sciancalepore, Maurizio; Prodam, Flavia; Papa, Amanda; Viri, Maurizio; et al. (Frontiers in Genetics, 2025)
IntroductionBalanced chromosomal abnormalities (BCAs) are structural variations that can underlie a wide spectrum of neurodevelopmental disorders, often remaining undetected by conventional diagnostic approaches. Whole-genome sequencing (WGS) allows for base-pair resolution of structural variants across the entire genome, making it a powerful tool to detect cryptic chromosomal rearrangements and refine breakpoint mapping. RNA sequencing (RNA-Seq), by enabling the detection of gene expression changes and fusion transcripts, provides complementary functional insights into the consequences of genomic alterations. This study integrated WGS and RNA-Seq to precisely characterize the breakpoints and assess the functional impact of de novo BCAs in two unsolved cases of Neurodevelopmental Disorders.Materials and methodsShort read WGS was used to identify the chromosomal breakpoints and gene disruptions caused by BCAs. RNA-Seq on blood RNA was employed to detect differential gene expression and potential fusion transcripts of disrupted genes.ResultsIn the first case, the inversion inv(8) (p11.2q13) disrupted two genes at the breakpoints, namely, CHD7 and SLC20A2. These genes are in opposite orientations, and the inversion realigned them in the same direction, generating two novel fusion genes. Disruption of CHD7 confirmed the suspected diagnosis of CHARGE syndrome. The interruption of SLC20A2, commonly associated with neurological symptoms, prompted further clinical evaluation. RNA-Seq identified in-frame fusion transcripts from the chimeric genes in the blood, suggesting a potential deleterious phenotypic effect. In the second case, WGS revealed a balanced translocation t(17; 22) (q25; q13) that disrupted EP300 at 22q25, confirming Rubinstein-Taybi syndrome. The concurrent disruption of RBFOX3 at 17q13 suggested additional neurological implications, particularly related to epilepsy. Transcriptomic analysis demonstrated the monoallelic and significantly reduced expression of EP300.ConclusionThese findings highlight the crucial role of WGS in identifying disease-associated BCAs and underscore the complementary value of RNA-Seq in assessing their functional consequences. This integrated approach enhanced diagnostic accuracy and clinical management, paving the way for more comprehensive and personalized care in these two patients.